Computational high entropy alloy design - Simelane Khombisile; Becker Thorsten Hermann (MATEC Web of Conferences)
Materials scientists are developing new materials to meet increasing demands by employing a systematic approach linking material performance to composition, processing, and microstructure. Computational techniques, such as Calculation of Phase Diagrams and Integrated Computational Materials Engineering, play a crucial role in this process, enabling fast and efficient material design. This study focuses on developing a high damage-tolerant high entropy alloy for hydrogen service, using the two computational techniques to identify optimal composition, predict mechanical properties, and elucidate strengthening mechanisms.